Demolir os muros dos pátios: a escritura de Maura Lopes Cançado como máquina de guerra, em O sofredor do ver - Brum, Deborah Regina Antunes (2021)
The title of this research, Demolish the courtyard walls: the scripture of Maura Lopes Cançado as a war machine, in O sofredor do ver, opens the path of this research that walks the smooth space of the creation. By reading the work of the author, Hospício é Deus and O sofredor do ver, it was possible to trace a line for this research, in which the aim is not the finishing line, but the path. Focusing on O sofredor do ver, the book of tales of Maura, I resort, mainly, to the concepts invented by Giles Deleuze and Félix Guattari to affirm the scripture of the author as a War machine, by which, through the writing, she deterritorializes herself from the spaces of confinement by reterritorializing in another space: the literary. In this trajectory, I noticed, and it was not a surprise, that the biographical facts of the author reverberate in reception, researches and critics about her work. Thus, the author is again silenced and confined to madness, which diminishes her potency as an author. Maura Lopes Cançado can not be reduced to a crazy writer, or a mad person. Maura, as an author, asks for voice in this trajectory - a path of two bodies, mine and hers, is also crossed by other ones, including the readers of this research. We make a rhizome. The Self(s) falls apart